Peran Pendidikan Agama Islam Dalam Membentuk Akhlak Karimah Siswa Di Era Revolusi Industri 4.0 Di MTS Banat Kudus - Maulina Istighfaroh; Nisaana 'Azzalatifa; Mu’awanah Mu’awanah (Universitas Muhammadiyah Surabaya, 2021)
Abstract 4.0 industrial revolution era is characterized by the development of increasingly sophisticated technology, especially in the field of communication. These positive impacts are accompanied by negative impacts. One of the negative impacts is the erosion of the character of students. For this reason, an effort is needed to improve the character of students in the 4.0 industrial revolution era by taking advantage of the role of Islamic religious education. Thus, the authors are interested in examining the role of Islamic religious education in shaping the character of students in the 4.0 industrial revolution era. This research uses a qualitative research approach and is descriptive in nature. The research was carried out at MTs NU Banat Kudus on March 10, 2021 by interviewing one of the moral teachers named Ms. Deti, S.Pd., in this study Ms. Deti stated that Islamic religious education, especially moral education, played a very important role in shaping the character of the students in this 4.0 industrial revolution era. This role is carried out side by side between teachers and schools. The role of the teacher is to remind and provide examples for students to always behave Keywords : morals, role, industrial revolution